Perceived ethical reputation: Scale development and validation - Silva, V.; Duarte, A.; Simões, E.; Neves, J. (Book of Abstracts of the 14th European Conference on Psychological Assessment (ECPA14), 2017)
Ethical reputation reflects organizations’ commitment to ethics (Jaramillo, Grisaffe, Chonko, & Roberts, 2009; Mulki & Jaramillo, 2011), based on perceived occurrences of ethical problems (Armstrong, 1996) and ways organizations treat their employees and customers (Dawkins & Lewis, 2003). Having a favorable reputation may lead to favorable consequences, such as attracting higher-quality applicants, enhanced job attitudes, and increased employee ethical conduct (Fombrun & Shanley, 1990; Turban & Cable, 2003). However, a comprehensive measure to assess employees’ perceptions of the ethical reputation of their organizations is still missing. Therefore, the present study attempts to develop and validate such a measure. A pool of items reflecting the different dimensions of the construct was drawn from the existing literature on business ethics and organizational reputation. The relevance and clarity of those items was assessed by experts to assure content validity. In order to assess the psychometric characteristics of the scale, data are being collected via convenience sampling. The target sample comprises employees from organizations of different business sectors. Subsequently, analyses to determine construct validity and reliability will be performed. Results will be presented at the conference. The present research is expected to provide a new and useful tool for measuring ethical reputation of organizations, to be used in future research on the issue.